Applications of Applied Mechanics to the Solution of Problems Connected with Transportation and Storage of Spent Nuclear Fuel. (2016) - Trebuňa, František; Šimčák, František; Bocko, Jozef
Abstract: The paper is devoted to description of methods and procedures of applied mechanics that are used for solution of problems connected with transportation and storage of spent nuclear fuel or other nuclear waste. The safety of nuclear fuel includes questions of cask reliability, safety of transport complex and problems of cooling of casks in a storage system. The solution of those problems is based on the numerical (finite element method) as well as experimental methods of mechanics.